2014
DOI: 10.1371/journal.pone.0106898
|View full text |Cite
|
Sign up to set email alerts
|

Educational Inequalities in Acute Myocardial Infarction Incidence in Norway: A Nationwide Cohort Study

Abstract: BackgroundIncreasing differences in cardiovascular disease (CVD) mortality across levels of education have been reported in Norway. The aim of the study was to investigate educational inequalities in acute myocardial infarction (AMI) incidence and whether such inequalities have changed during the past decade using a nationwide longitudinal study design.MethodsData on 141 332 incident (first) AMIs in Norway during 2001–2009 were obtained through the Cardiovascular Disease in Norway (CVDNOR) project. Educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
7
23
0
1
Order By: Relevance
“…That relative inequalities were greater in mid-age (45–64 years) than older people—across the various outcomes and the different measures of SEP—is in line with previous international evidence [15, 16, 23, 25, 39, 48]. This attenuating RR will occur wherever absolute risk increases with increasing exposure (as is usually the case with age) and RDs remain constant (and in some cases even if RDs rise).…”
Section: Discussionsupporting
confidence: 86%
“…That relative inequalities were greater in mid-age (45–64 years) than older people—across the various outcomes and the different measures of SEP—is in line with previous international evidence [15, 16, 23, 25, 39, 48]. This attenuating RR will occur wherever absolute risk increases with increasing exposure (as is usually the case with age) and RDs remain constant (and in some cases even if RDs rise).…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies found that patients with low SES have significantly higher risk of an outcome or death due to a chronic disease, including chronic obstructive pulmonary disease outcomes, cardiovascular disease [ 18 20 ]. Similar results were found for ACS, where the lowest SES group had the highest rates of MI and death due to coronary heart disease [ 21 ]. When it seems appropriate for those with ACS and low SES to be treated more rigorously compared to those with high SES, some studies have reported that patients in the lowest SES group were disadvantaged in receiving some guideline recommended discharge medication prescriptions [ 12 16 ].…”
Section: Introductionsupporting
confidence: 78%
“…One possible explanation could be that lower education had a relationship with the patients' health literacy skills (Igland et al . ). Indirectly, low health literacy is often linked to a poorer socio‐economic status, which in turn is associated with adverse health outcomes (Sørensen et al .…”
Section: Discussionmentioning
confidence: 97%
“…The education level is considered to be an indicator of socio‐economic status (Igland et al . ) and lower education has been associated with long‐term pain (Hinrichs‐Rocker et al . , Langley ).…”
Section: Discussionmentioning
confidence: 99%